2015
DOI: 10.1038/cmi.2014.131
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alpha (IFNα)-induced TRIM22 interrupts HCV replication by ubiquitinating NS5A

Abstract: TRIM22, a tripartite-motif (TRIM) protein, is upregulated upon interferon alpha (IFNa) administration to hepatitis C virus (HCV)-infected patients. However, the physiological role of TRIM22 upregulation remains unclear. Here, we describe a potential antiviral function of TRIM22's targeting of the HCV NS5A protein. NS5A is important for HCV replication and for resistance to IFNa therapy. During the first 24 h following the initiation of IFNa treatment, upregulation of TRIM22 in the peripheral blood mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 35 publications
3
75
0
Order By: Relevance
“…TRIM14 and TRIM22 are two TRIMs that function as ISGs during hepatitis C virus (HCV) infection [78,79]. The presence of either TRIM14 or TRIM22 conferred restriction against HCV replication that depended on an interaction with the viral NS5A protein in both cases [78,79]. This interaction resulted in the destruction of the viral NS5A by ubiquitination and subsequent proteasome targeting [78,79].…”
Section: Proteasome-dependent Antiviral Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM14 and TRIM22 are two TRIMs that function as ISGs during hepatitis C virus (HCV) infection [78,79]. The presence of either TRIM14 or TRIM22 conferred restriction against HCV replication that depended on an interaction with the viral NS5A protein in both cases [78,79]. This interaction resulted in the destruction of the viral NS5A by ubiquitination and subsequent proteasome targeting [78,79].…”
Section: Proteasome-dependent Antiviral Mechanismsmentioning
confidence: 99%
“…The presence of either TRIM14 or TRIM22 conferred restriction against HCV replication that depended on an interaction with the viral NS5A protein in both cases [78,79]. This interaction resulted in the destruction of the viral NS5A by ubiquitination and subsequent proteasome targeting [78,79]. Although TRIM14 is known to function as a mitochondrial adaptor for IFN and NF-κB signalling, usage of the TRIM14 mutant that fails to mediate innate immune signalling (K365R) revealed restriction against HCV was unaltered [78].…”
Section: Proteasome-dependent Antiviral Mechanismsmentioning
confidence: 99%
“…TRIM22 inhibits the transcription and replication of HIV‐1 via blocking the long terminal repeats and disrupting intracellular transport of GAG protein (Barr et al, ). In addition, TRIM22 is also proven to be resistant to Influenza A virus by targeting the viral nucleoprotein for degradation (Di et al, ), Hepatitis C (HCV) by ubiquitinating NS5A (Yang et al, ), HBV through its single CpG methylation (Lim et al, ). These findings reveal an important role of TRIM22 as a RF in intrinsic antiviral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 First, we tested the effects of Rubicon overexpression and knockdown on cell viability. Our results demonstrated that neither condition significantly influenced the growth of Huh7 cells (data not shown).…”
Section: Rubicon Affects the Expression Of Ifns And Ifn Downstream Efmentioning
confidence: 99%